MEMPERTEMUKAN PERJANJIAN SINAI KEPADA MASYARAKAT GEREJA - Feri Aman Mendrofa (JURNAL TABGHA, 2022)
The Sinai Covenant was very important in the life of the Israelites. Through this covenant, God gave His statutes as the creator God, also the Israelites had the privilege of being the chosen people. This blessing that was given to the nation of Israel was also given to the church. Realizing this, the church must prepare the congregation to accept it. The inability of the church to understand the promise will fail the church in carrying out its duties properly. In the Sinai covenant, God was the creator who made the nation of Israel his own, a kingdom of priests and a holy nation (Exodus 19: 5). This covenant separates the identity of the Israelites as God's chosen people. The church as a fellowship ordained by God also enjoys this blessing (1 Peter 2:9). The purpose of this study is to make it easier for readers to understand how to see the relationship between the Sinai covenant between God and Israel and God's covenant with the church. The sources of this research are taken from various books of interpretation and biblical theology of the Old Testament and the New Testament.